2021
DOI: 10.3389/fneur.2020.577312
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood and Salivary Biomarkers of Blood–Brain Barrier Permeability and Neuronal Damage: Clinical and Applied Concepts

Abstract: Within the neurovascular unit (NVU), the blood–brain barrier (BBB) operates as a key cerebrovascular interface, dynamically insulating the brain parenchyma from peripheral blood and compartments. Increased BBB permeability is clinically relevant for at least two reasons: it actively participates to the etiology of central nervous system (CNS) diseases, and it enables the diagnosis of neurological disorders based on the detection of CNS molecules in peripheral body fluids. In pathological conditions, a suite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 246 publications
1
49
0
Order By: Relevance
“…Biomarkers in traumatic brain injury may be sampled from blood, cerebrospinal fluid, brain interstitial fluid collected during brain microdialysis and most recently, saliva. Preliminary studies have shown that there is a correlation between salivary and serum S100B (14,15). The greatest contribution to the peripheral signal most likely comes from those brain cell biomarkers derived from the brain interstitial fluid and cerebrospinal fluid.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarkers in traumatic brain injury may be sampled from blood, cerebrospinal fluid, brain interstitial fluid collected during brain microdialysis and most recently, saliva. Preliminary studies have shown that there is a correlation between salivary and serum S100B (14,15). The greatest contribution to the peripheral signal most likely comes from those brain cell biomarkers derived from the brain interstitial fluid and cerebrospinal fluid.…”
Section: Biomarkersmentioning
confidence: 99%
“…Traumatic brain injury is the commonest cause of death and disability amongst children greater than one year of age (1) and continues to present complex management and prediction challenges for the clinician. Traumatic brain injury is commonly classified into mild [Glasgow Coma Score (GCS) [13][14][15], moderate (GCS 9-12) or severe (GCS 3-8) based on the GCS. TBI should not be viewed as a single pathophysiological event, but a cascade that involves two separate injury phases, primary and secondary (2).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that S100B is increased by exercise alone (13,25,26), while others found no effect of strenuous exercise on S100B levels (27)(28)(29)(30)). An explanation of these contrasting ndings points to BBB damage induced by extreme exercise (31). According to this hypothesis, strenuous exercise or performance in extreme sports results in BBB "opening," possibly due to a mechanism involving free radical formation, as suggested by ref.…”
Section: Introductionmentioning
confidence: 97%
“…(32). In any case, it is not known how different sources of S100B contribute to the peripheral signal in blood (or saliva) (26,31,33,34). Lastly, a common motif in S100B diagnostics is that S100B is not speci c for any neurological disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, fluids [8], such as blood [9], saliva [9], urine [10], and cerebrospinal fluid (CSF) [11] and brain imaging techniques, such as structural MRI [12] and PET [13] have been used to establish a disease diagnosis and predict disease outcomes. Although CSF analysis is key in AD diagnosis, the moderately invasive nature of CSF collection limits its widespread use in routine primary clinical care practice, as the procedure is rarely performed by general practitioners [14].…”
Section: Introductionmentioning
confidence: 99%